Surgical Checklist Implementation Project: The Impact of Variable WHO Checklist Compliance on Risk-adjusted Clinical Outcomes After National Implementation. Issue 1 (January 2016) - Mayer, Erik K.; Sevdalis, Nick; Rout, Shantanu; Caris, Jochem; Russ, Stephanie; Mansell, Jenny; Davies, Rachel; Skapinakis, Petros; Vincent, Charles; Athanasiou, Thanos; Moorthy, Krishna; Darzi, Ara
Abstract : Objective: To evaluate impact of WHO checklist compliance on risk-adjusted clinical outcomes, including the influence of checklist components (Sign-in, Time-out, Sign-out) on outcomes. Background: There remain unanswered questions surrounding surgical checklists as a quality and safety tool, such as the impact in cases of differing complexity and the extent of checklist implementation. Methods: Data were collected from surgical admissions (6714 patients) from March 2010 to June 2011 at 5 academic and community hospitals. The primary endpoint was any complication, including mortality, occurring before hospital discharge. Checklist usage was recorded as checklist completed in full/partly. Multilevel modeling was performed to investigate the association between complications/mortality and checklist completion. Results: Significant variability in checklist usage was found: although at least 1 of the 3 components was completed in 96.7% of cases, the entire checklist was only completed in 62.1% of cases. Checklist completion did not affect mortality reduction, but significantly lowered risk of postoperative complication (16.9% vs. 11.2%), and was largely noticed when all 3 components of the checklist had been completed (odds ratio = 0.57, 95% confidence interval: 0.37–0.87, P  < 0.01). Calculated population-attributable fractions showed that 14% (95% confidence interval: 7%-21%) of the complications could be prevented if full completion of the checklist was implemented. Conclusions: Checklist implementation was associated with reduced case-mix-adjusted complications after surgery and was most significant when all 3 components of the checklist were completed. Full, as opposed to partial, checklist completion provides a health policy opportunity to improve checklist impact on surgical safety and quality of care. Abstract : Supplemental Digital Content is available in the text